2008
DOI: 10.1111/j.1365-2702.2007.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing information: users’ experiences of a system in Taiwan one year after its implementation

Abstract: L E E T -T ( 2 0 0 8 ) L E E T -T ( 2 0 0 8 ) Journal of Clinical Nursing 17, 763-771 Nursing information: users' experiences of a system in Taiwan one year after its implementation Aim and objective. The purpose of this study was to explore nurses' experiences during the first year of the installation of a nursing information system (NIS). The objective was to identify the major issues that emerged regarding the users' concerns of this technology in their daily practice. Background. The success of the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 39 publications
(100 reference statements)
1
31
0
Order By: Relevance
“…Sheikh et al (2011) highlighted the slower than expected implementation of EHRs nationally and the students' experiences confirmed that implementation is incomplete, with no EHRs in some settings. A further barrier, encountered by about a quarter of students, was insufficient computers available, a result supporting previous research (Lee, 2008;Mahon et al, 2010).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Sheikh et al (2011) highlighted the slower than expected implementation of EHRs nationally and the students' experiences confirmed that implementation is incomplete, with no EHRs in some settings. A further barrier, encountered by about a quarter of students, was insufficient computers available, a result supporting previous research (Lee, 2008;Mahon et al, 2010).…”
Section: Discussionsupporting
confidence: 66%
“…Internationally, EHR systems are being implemented and evaluated (Lee, 2008;Green and Thomas, 2008;Zwaanswijk et al, 2011). In 2002, England's Department of Health proposed a strategy for a national EHR system and in 2005, the NHS 'Connecting for Health' was formed to support the EHR agenda.…”
Section: Introductionmentioning
confidence: 99%
“…This cannot be done with the traditional randomized control trial methodology. While early studies of clinical information needs focused on physicians, more recent studies have found that nurses' information needs differ from those of physicians, and may include information about protocols and procedures [7], drug therapy, and diagnosis [8]. Nursing responsibilities in healthcare organizations run the gamut from educating patients to medication administration to executing physician orders and ensuring safety.…”
Section: Introductionmentioning
confidence: 98%
“…Nursing is not only a care giving profession, but has become a technology-proficient profession as well (Lee, 2008). In this context, Staggers et al (2002) produced a research based master list of informatics competencies for nurses of four levels: beginning nurses, experienced nurses, informatics specialists, and informatics innovators.…”
Section: Introductionmentioning
confidence: 99%
“…Besides producing, processing, storing, distributing and using information, the computers increase the level of learning by simultaneously addressing several senses, create permanent learning, save from time, place and learning speed and support life-long learning. With such attributes, the computers support efficient fulfillment of the roles, functions and responsibilities of the nurses/in-service training nurses, increase the quality of health care and enhance quality and efficiency of nursing practice (McNeil et al, 2003;Jiang et al, 2004;Lee, 2008;ANCC, 2010;Chow et al, 2011;Kaya, 2011;Lın et al, 2014).…”
Section: Introductionmentioning
confidence: 99%